«Mujer y tigre»: influence of the Catholic religion in the creation of Peruvian colloquial expressions - Marín Rodríguez, Jimena Alondra (2022)
This article will analyze how Catholicism has influenced the formation of colloquial expressions during the Viceroyalty and how these are still valid today. For this purpose, we will focus on the tradition «Mujer y tigre», a text in which Ricardo Palma refers to the importance of the Catholic religion in the viceroyalty society, as well as its influence on interpersonal relationships. In this sense, we will identify the idioms in which faith and worship prevailed. Finally, it will be mentioned the way in which the Catholic creed has intervened in the forms and customs expressed in colloquial sayings and proverbs related to the role of women during that time.